Filmography of social issues a reference guide - Mitchell, Charles P. 1949-; Gale Group (Westport, Conn. Greenwood Press, 2004)
Examines twenty specific social themes and shows how they are examined in a hundred motion pictures. Intended to serve as a guide for individuals interested in motion pictures and how they reflect and comment on the major issues of our time.
Electronic reproduction.
Keywords: Motion pictures and history; Social problems in motion pictures; Motion pictures -- United States -- Plots, themes, etc; Electronic books